Argumentando sobre a argumentação na entrevista motivacional : uma discussão pela análise do comportamento - Bezerra, Caroline de Paula Corrêa (2014)
This thesis has the argument as its theme and contains two inter-dependent papers. The first is a theoretical one and exposes a behavioral definition of argument approaching it to the linguistic definition, observing the characteristics of the settings in which behavior analysts and linguists complement each other. From a systematic review of the literature on argumentation in Linguistics and from a theoretical research on the topic in Behavior Analysis, the results show that the argument can be conceptualized in Behavior Analysis as speaker's verbal behavior under the control of the listener to produce change in his/her behavior, presenting in emissions of mand, tact, and especially autoclitic functions. The functionalist approach to Linguistics (in particular, pragmatism) contributes to understanding the argumentation for Behavior Analysis. The second paper applies the concept of argumentation obtained in the first article in the analysis of the functions of the argumentation process in host groups on a Psychosocial Care Center Alcohol and other Drugs (CAPSad), based on Motivational Interviewing (MI). To this end, eight group sessions in the CAPSad were collected focusing on the behavior of two professionals. Data were transcribed and submitted to the Behavioral Analysis of Discourse. As a result, from its functional definition, there is argumentation in the MI technique, although it is contraindicated by the technique. This finding allows the rapprochement between theories to discuss and assume the argumentation and its applicability in the drug field. Finally, it was concluded that both papers contribute to approximate Behavior Analysis yields to argumentation research in other sciences.